Amethyst occurrences in Tertiary volcanic rocks of Greece: mineralogical and genetic implications - Voudouris, P.; Psimis, I.; Mavrogonatos, C.; Kanellopoulos, C.; Kati, M.; Chlekou, E. (Bulletin of the Geological Society of Greece, 2013)
Epithermal-altered volcanic rocks in Greece host gem-quality amethyst veins in association with various silicates, carbonates, oxides, sulfides and halides. Host rocks are Oligocene to recent calc-alkaline to shoshonitic lavas and pyroclastics of intermediate- to acid composition. The amethyst-bearing veins occur in the periphery of porphyry-type and/or high-sulfidation epithermal mineralized centers in northern Greece (e.g. Sapes, Kirki, Kornofolia/Soufli, Lesvos island) and on Milos island in the active Aegean Volcanic Arc. Hydrothermal alteration around the quartz veins includes sericitic, K-feldspar (adularia), argillic, propylitic and zeolitic types. Precipitation of amethyst in the northern Greece occurrences, took place during the final stages of the magmatic-hydrothermal activity from near-neutral to alkaline fluids, as indicated by the presence of gangue adularia, calcite, smectite, chlorite, sericite, pyrite, zeolites (laumontite, heulandite, clinoptilolite), analcime and minor amounts of barite, halite, epidote and fluorite in the quartz veins. Amethyst at Milos Island (Chondro Vouno and Kalogries-Vani areas), is accompanied by barite, smectite and lepidocrocite. Colloform-crustiform banding with alternations of amethyst, chalcedony and/or carbonates is a common characteristic of the studied amethyst-bearing veins. Fluid inclusion- and mineralogical data suggest that the studied amethyst were formed at: 174-246 °C (Sapes area), 100-175 °C (Kirki and Kornofolia areas) and 223-234°C (Lesvos island). The amethyst formation requires oxidizing conditions and is probably the result of mixing between meteoric or seawater with upwelling hydrothermal fluids. The involvement of seawater in the studied mineralization is supported by the presence of halite and abundant barite in the veins. Finally, the studied amethyst deposits should be evaluated as potential gemstone sources in Greece.